The Effect of Different Dynamic Stretching Exercise Durations on Different Agility Performances in Judokas - Eken, Özgür; Bayer, Ramazan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dynamic stretching exercises performed before competition or training can contribute to improve performance in athletes. However, there may be differences in performance development depending on the duration of the stretching exercises. Aim: The purpose of this study is to evaluate the effect of different dynamic stretching exercise durations on different agility performances in judokas. Methods: Twelve male athletes between 18-25 years old, who exercised judo regularly for three days a week for at least 3 years (age, 21.42± 1.97 years; body height, 173.25± 3.13 cm; body weight 69.25± 2.98 kg; BMI 23.16±.39) participated in the study. Judokas’ exercise protocols consisted of 5MDS (5 minutes of jogging + 5 minutes of dynamic stretching), 10MDS (5 minutes of jogging + 10 minutes of dynamic stretching) and 15MDS (5 minutes of jogging + 15 minutes of dynamic stretching) exercise protocols in consecutive days. After DS exercise, T-test agility, 505 agility and Illinois agility tests were performed. Results: There was a significant improvement in the performance of T test agility [F (1,595)= 19,184 p=.000, ηp 2: ,636], 505 agility test [F(1,703)= 9.448 p=.002, ηp 2: ,462] and Illinois agility test [F(1.419), p=.003, ηp 2: ,493] after 10MDS, 15MDS and 5MDS exercise protocols, from low to high, respectively. In addition, a significant difference was found between 5MDS, 10MDS and 15MDS exercise protocols (p<.05). Conclusion: According to the results of the study, it can be recommended that male judokas could perform 10MDS exercises before competition or training to improve their agility performance. On the contrary, 5MDS exercise is not recommended for judokas to improve their agility performance.